Struktur Komunitas Plankton di Pantai Tanjung Bastian Timor Tengah Utara - Priyambodo, Hernur Yoga; Santiari, Made (Biocaster : Jurnal Kajian Biologi, 2025)
Tanjung Bastian Beach is one of the coastal areas in North Central Timor Regency where plankton research has never been conducted. Plankton data is essential for formulating sustainable coastal management strategies. The purpose of this study was to determine the plankton community structure and the physicochemical parameters of the waters at Tanjung Bastian Beach. This study employed a quantitative descriptive design. There were three research stations consisting of a mangrove ecosystem and a coastal ecosystem. Plankton was collected using a 20 μm plankton net, and the physicochemical parameters were measured using a water quality tester. The results showed that Grammatophora sp., Synedra sp1., Synedra sp2., Cyclops sp1., Cyclops sp2., and Nauplius sp. were found at all stations. The abundance of phytoplankton and zooplankton indicated that the three stations were classified as oligotrophic to eutrophic waters. The phytoplankton diversity index value ranged from 1.91 to 2.10, indicating moderate water pollution or moderate community stability. The zooplankton diversity index ranged from 0.96 to 0.99, indicating an unstable biota community or severely polluted water quality. However, at station 3, the index was 1.08, indicating moderate biota community stability or moderately polluted water quality. The phytoplankton and zooplankton evenness index ranged from 0.87 to 0.98, indicating high uniformity with a stable community. A dominance index value <0.5 indicates no dominant species. Physicochemical parameters support plankton life.